PENGARUH SISTEM PENGENDALIAN INTERNAL DAN TEKNOLOGI INFORMASI TERHADAP NILAI LAPORAN KEUANGAN (STUDI PADA PUSKESMAS KABUPATEN SAMBAS) - Marija; Elita Darmasari; Hermi Sularsih; Risnaningsih (Universitas Prof.Hazairin,SH Bengkulu, 2024)
Abstract The research was conducted to see the influence of the internal control system and information technology on the quality of financial reports. This type of research was carried out using a quantitative approach with a sample size of 46 people consisting of the head of the administrative sub-division and the treasurer for cash expenditures at the Community Health Center in Sambas Regency. The research method used is the multiple linear regression analysis method and SPSS 25 statistical software. The research results show that the internal control system and information technology significantly influence the value of financial reports.